The relationship between personality traits and performances of potential paddy farmers in IADA Rompin, Pahang - Mustafa, Siti Norbazilah (2018)
The paddy and rice sector has been a strategic sector and always getting a special management by the government of Malaysia. Furthermore, rice is the staple food for all people in Malaysia’s with the total population was estimated at 31.7 million persons. Hence, the government took an action to build new granary areas by upgrading the existing granary in Malaysia; which are IADA Rompin, IADA Pekan, IADA Kota Belud and IADA Batang Lupar. The objectives for this study are to investigate the level of personality traits and work performances of potential paddy farmers; to determine the relationship between personality traits and work performances of potential paddy farmers; and to identify the personality traits that most influences affect the working performances. The study was conducted in one of the new granary areas which are IADA Rompin, Pahang. The total respondents involved are 158 from 1103 paddy farmers in Paya Setajam and Paya Sepayang which using the stratified selection for respondents. The data was collected using a surveying method with the instrument of questionnaire which comprised of 4 sections. All the data analyzed using software of Statistical Package for the Social Sciences version 23 (SPSS 23) for analysis of descriptive, correlation coefficient and linear regression. Result indicated that the level of personality traits and work performances of potential paddy farmers was at the moderate levels. Well-disciplines and ability for solving a problems are highly significant towards work performances. However, all the personality traits shows a positive a relationship towards work performances and the strongest influences personality traits to the performances of potential paddy farmers was well-disciplines.